INGGRIS - Azis, Nur Dwika Cahyanti; H, Herman; Niswaty, Risma (International Journal Of Public Policy and Bureaucracy, 2024)
Malino has the potential for tourism areas in Gowa Regency, but tourism development in this area still needs further action. Therefore, to realize this potential, various strategies and developments are needed, as well as sustainable management from the government in collaboration with the community. The existence of this strategy and development will not only increase tourist attraction, but will also make a major contribution to increasing the Regional Original Income (PAD) of Gowa Regency. This study aims to produce an accurate picture of how the Malino tourism development strategy is in increasing the regional original income at the Gowa Regency Tourism and Culture Office and the factors that support and inhibit the Malino tourism development strategy in increasing the regional original income of Gowa Regency. The type of research is descriptive qualitative research with data collection techniques, namely interviews, observations, and documentation. The checking of data validity is carried out through source triangulation. Data analysis techniques use data condensation, data presentation, and drawing conclusions. The results of the study indicate that effective planning for tourism development in Malino in increasing the Regional Original Income (PAD) in Gowa Regency involves infrastructure development, improving service quality, and nature-based and cultural tourist attractions. Integration of digital media promotion and collaboration with the private sector strengthens Malino's attractiveness as a tourist destination. Development of local resource capacity supports sustainable tourism and increases visitor arrivals. Factors influencing the effectiveness of tourism strategies in Malino include rich natural potential, government commitment, and local community involvement. Challenges such as budget constraints, inadequate infrastructure, and environmental awareness exist but do not hinder the overall success in increasing the Local Revenue (PAD) of Gowa Regency. Based on the components of Burhalis' theory (2000), namely, Attractions, Accessibility, Amenities, Accommodation, Activities, Ancillary Suervices, have been implemented well. However, the components of the Accessibility and Amenities theory still require some improvements in order to create an efficient and effective tourism strategy and development so as to increase the Local Revenue (PAD) of Gowa Regency. Keywords: Strategy, Tourism Development, PAD